How Can Prosocial Behavior Be Motivated? The Different Roles of Moral Judgment, Moral Elevation, and Moral Identity Among the Young Chinese - Ding, Wan; Shao, Yanhong; Sun, Binghai; Xie, Ruibo; Li, Weijian; Wang, Xiaozhen (Frontiers in Psychology, 2018)
Prior research has shown that moral judgment, moral elevation, and moral identity contribute to prosocial behavior. However, how these three motivating factors interact in predicting prosocial behaviors is not yet clear. The current study proposed and examined a moderated mediation model to illustrate the specific process of how prosocial behavior is motivated by these factors. A total of 264 Chinese undergraduate and graduate students participated in the present study (140 females; age range 17–26, M = 20.25, SD = 1.57). Moral judgment competence, intensity of moral elevation, and moral identity were measured by self-reported scales, and the tendency to engage in prosocial behavior was assessed in a simulated “Ask for help” situation. The multiple regressive results showed that moral elevation mediated the effect of moral judgment on prosocial behavior, and moral identity moderated this mediation through interacting with moral elevation. However, within the proposed model, the mediating effect of moral elevation was stronger in women than in men, while the moderating role of moral identity appeared only in women. These findings imply different methods for men and women to enhance their prosocial behaviors, including the need to pay more attention to developing moral reasoning in men while putting more emphasis on evoking moral emotion and moral traits in women. Together, these results supported the assumptive model and provided a comprehensive framework to explain prosocial behaviors.